Compensation algorithms based on the p-q and CPC theories for switching compensators in micro-grids - Monteiro, Luís F. C. (2009)
The main objective of this paper is to com-pare the applicability and p erformance of a switching compensator when it is controlled by algorithms derived from the pq–Theory and from the Current’s Physical Components Power Theory (CPC-Theory) considering a micro-grid application. Compensation characteristics derived from each one of these set of power definitions are highlighted, and simulation results of test cases are shown. Special attention is put on the oscillating instan-taneous real power, as it may produce torque oscillations or frequency variations in weak systems (micro-grids) generators. The oscillating instantaneous real power, as defined in the pq-Theory, gives the amount of energy oscillating between the source and the load, and its com-pensation using a switching compensator must have an energy storage element to exchan ge it with the load. The energy storage element can be ea sily calculated with the pq-Theory.